Mengontrol Dominasi TV Swasta di Indonesia - Priliantini, Anjang (Jurnal Ilmu Komunikasi, 2023)
The aim of this research is to provide an overview of the phenomenon of media conglomeration and convergence in Indonesia, and to try to construct solutions to save public space through diversity of ownership and diversity of content. The results of this research show that media conglomeration and convergence will be profitable for media owners, and conversely create losses for the public. One of the reasons why the public is disadvantaged in this phenomenon is due to the weakness of media regulations so that they can be exploited by media owners. In fact, the public has the right to obtain diverse information without interference from media owners.